Mathematical Connection Profile of Junior High School Students in Solving Mathematical Problems based on Gender Difference (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aimed at describing the mathematical connection profile of Junior High School students in solving mathematical problems based on gender difference. The subjects were two eighth grade students who had the same math ability. They were one male student and one female student. Subjects were selected by giving a math ability test, and based on the same scores at a middle level. The research type was exploration with a qualitative approach. Data were taken by interviewing the subject in depth on the basis of Task problem-solving. The problem-solving task contained narrative matter related to Geometry matter and Social Arithmetic. Data credibility used time triangulation. Data analysis was done by data categorization, data reduction, data display, data interpretation, and conclusion. The research results showed that male student connected and used mathematical ideas in the Abstrak : Penelitian ini bertujuan untuk men deskripsikan profil koneksi matematis siswa Sekolah Menengah Pertama dalam memecahkan masalah matematika berdasarkan perbedaan gender.form of facts, concepts/principles, and mathematical symbols in sufficient quantity, and they were linked appropriately and the mathematical ideas connection were used effectively so that it could solve problems correctly. The female student made a connection with mathematical ideas in excessive quantity and the connection was not appropriate, so the student could not solve the problem correctly. This indicated that mathematical connection profile of male student in solving mathematical problems was an efficient, strong, and effective category. On the other hand, the mathematical connection profile of female student in solving mathematical problems was in the category of inefficient, weak, and ineffective. From this result, it is suggested to the math teachers to create a learning process that is able to facilitate all students to practice improving their mathematical connection ability so they are able to succeed in solving mathematical problems.